“To how many shameful deeds must you lend your image”: Schubert’s Pattern of Telescoping and Excision in the Texts of His Latin Masses - Gingerich, John (Current Musicology, 2000)
A constant of Schubert reception has been the image of an unintellectual composer. From the early stories of songs gushing from his pen at near-performance tempo, to the Biedermeier Liederfiirst, and the shy but good-natured tippler of Dreimiiderlhaus, an image of subconscious creativity became wedded to a popular persona of childlike innocence: tubby, chubby, bespectacled Schwammerl, slightly befuddled in a lovably helpless way, shielded from the harsh cares and calculations of this world by an absent-minded preoccupation with beautiful melody and convivial drink. This image of Schubert, long uncontroversial, now seems at best risibly quaint. Nevertheless, its grip remains deceptively tenacious. The more recent emphasis on Schubert’s darker side-his unruly sexuality, his alienation, his venereal disease, his preoccupation with death-has reinforced the ambient image of Schubert as a creature of instinctual drives, and concomitantly, of somnambulant, clairvoyant creativity. The deep current of Schubert’s reception as an instinctive genius sustains the new eddies swirling around Schubert the self-indulgent hedonist. Beneath the turbulent surface, Schubert, no longer childlike, remains innocent of sustained and serious thought.